Cryoapparatus with Embedded Superconductive Solenoid for Studying the Magneto- and Electro-Physical Properties - Zharkov, I.P.; Safronov, V.V.; Palamarchuk, S.P.; Pylypchuk, O.S.; Solonetsky, A.G.; Khodunov, V.O. (Science and Innovation, 2024)
Complex cryogenic equipment based on temperature-controlled helium cryostat with a superconducting embedded solenoid for studying the galvanic and magnetic phenomena in 2D systems has been designed. It ensures the temperature control of studied sample within the ranges of 1.6-4.2; 4.2-80; and 80-300 К and the temperature stability in the magnetic field of up to 7.84 T with an accuracy of 0.1 K, at most.